Question about SoftMath Algebrator - Algebra Homework Solver (689076614429)

In algebra there are some identities (that are true all the time(.

(a+b)^2 is always equal to a^2+2ab+b^2, regardless of the values of a and b. Another one (**a-b)^2=a^2-2ab+b^2**, and **a^2-b^2=(a-b)(a+b)**

There is also the binomial identity (a+b)^n. Look this one up.

(a+b)^2 is always equal to a^2+2ab+b^2, regardless of the values of a and b. Another one (

There is also the binomial identity (a+b)^n. Look this one up.

Jun 07, 2014 | Educational & Reference Software

In algebra there are some identities (that are true all the time)

**(a+b)^2 is always equal to a^2+2ab+b^2**, regardless of the values of a and b. Another one **(a-b)^2=a^2-2ab+b^2**, and

**a^2-b^2=(a-b)(a+b)**

There is also the binomial identity**(a+b)^n.** Look this one up.

There is also the binomial identity

Jun 05, 2014 | Educational & Reference Software

Assume that the letter "a" represents the number of 7th graders.

Since there are twice as many 6th graders we can call them "2a".

There are 57 total members, we can make the following statement:

2a + a = 57

We can simplify this to say 3a = 57.

Divide 57 by 3 = 19. (this is the value of "a")

There are 19 seventh graders and 19 x 2 sixth graders or 38.

38 + 19 = 57

Since there are twice as many 6th graders we can call them "2a".

There are 57 total members, we can make the following statement:

2a + a = 57

We can simplify this to say 3a = 57.

Divide 57 by 3 = 19. (this is the value of "a")

There are 19 seventh graders and 19 x 2 sixth graders or 38.

38 + 19 = 57

Sep 20, 2013 | M2K Garfield: It's All About Math Math...

1. Combine like terms on the left side of =

4x-2x =2x

New left side is 2x + 1

2. Combine like terms on right side of =

5 - 7 = -2

New right side is x - 2

3. New problem is 2x + 1 = x - 2

4. Now get all x terms on left side of =

and all constants on right side of = by adding the opposites of the corresponding terms as you move them across the =

2x - x = -2 - 1

5. Combine the like terms on each side of the =

Left side: 2x - x = x and Right side: -2 -1 = -3

So x = -3

6. Now check your solution by substituting your answer back in to the original problem.

4(-3) - 2(-3) + 1 = 5 + (-3) -7

7. Now do the arithmatic and hopefully the left and right sides are equal.

-12 + 6 +1 = 5 -3 -7

-5 = -5

Since this is a true statement I know my answer of x = -3 is the correct solution to this problem.

4x-2x =2x

New left side is 2x + 1

2. Combine like terms on right side of =

5 - 7 = -2

New right side is x - 2

3. New problem is 2x + 1 = x - 2

4. Now get all x terms on left side of =

and all constants on right side of = by adding the opposites of the corresponding terms as you move them across the =

2x - x = -2 - 1

5. Combine the like terms on each side of the =

Left side: 2x - x = x and Right side: -2 -1 = -3

So x = -3

6. Now check your solution by substituting your answer back in to the original problem.

4(-3) - 2(-3) + 1 = 5 + (-3) -7

7. Now do the arithmatic and hopefully the left and right sides are equal.

-12 + 6 +1 = 5 -3 -7

-5 = -5

Since this is a true statement I know my answer of x = -3 is the correct solution to this problem.

May 17, 2012 | SoftMath Algebrator - Algebra Homework...

**Solve (***x*+ 2)(*x*+ 3) = 12.

- It is very common for students to see this type
of problem, and say:

solve to get x = 10 and x = 9. That was easy!"

So, tempting though it may be, I cannot set each of the factors above equal to the other side of the equation and "solve". Instead, I first have to multiply out and simplify the left-hand side, then subtract the 12 over to the left-hand side, and re-factor. Only then can I solve.

- (

(

Jul 17, 2011 | H. B. Enterprises Quadratic Solver

Here, We deal with Some Special Products in Polynomials.

Certain products of Polynomials occur more often

in Algebra. They are to be considered specially.

These are to be remembered as Formulas in Algebra.

Remembering these formulas in Algebra is as important

as remembering multiplication tables in Arithmetic.

We give a list of these Formulas and Apply

them to solve a Number of problems.

We give Links to other Formulas in Algebra.

Here is the list of Formulas in

Polynomials which are very useful in Algebra.

Formulas in Polynomials :

** Algebra Formula 1 in Polynomials: ** * Square of Sum of Two Terms: *

** (a + b)2 = a2 + 2ab + b2 **

** (a - b)2 = a2 - 2ab + b2 **

** (a + b)(a - b) = a2 - b2 **

** (a + b)(a2 - ab + b2) = a3 + b3 **

** (a - b)3 = a3 - 3a2b + 3ab2 - b3 = a3 - 3ab(a - b) - b3 **

(First term + Second term)2

= (First term)2 + 2(First term)(Second term) + (Second term)2

Jul 02, 2011 | Educational & Reference Software

Compare the terms of the product of the square of binomial and the terms of the product of the sum and difference of two terms. What statements can you make?

Jun 16, 2011 | Educational & Reference Software

Hmmm ... 15/60

Since 60 can be divided evenly by 15, then let's start there:

15 divided by 15 is equal to 1. (correct?)

60 divided by 15 is equal to 4. (correct?)

Then:

15/60 =

(by the way, the common divisor is 15)

Aug 14, 2010 | Mathsoft Solving and Optimization...

It depends on how complex the function is; there are different techniques. For a straight line of the standard form, usually shown as y=mx+b; this is a simple function of y in terms of x. So, determining the function in this case means finding values for m and b. --- m is the slope of the line, commonly called rise over run. Since your question asks in terms of coordinates, I would assume that you are looking at a problem giving you 2 points.

Probably something like p1 = (3,4); p2 = (5,8); the general form of this is p1=(x1,y1); p2=(x2,y2). The slope in this case is rise over run, in other words, the change in y divided by the change in x. This can be calculate between these two points as (y2-y1)/(x2-x1). In my sample above, this would be (8-4)/(5-3) = 4/2 = 2 giving the value of m.

To find the value of b (the y intercept) you need the value of y when x = 0. Since you already know that m, the slope is 2, consider a new point, call it p3 (x3,y3), pick either of the known points and solve the slope equation again, this time for y3. [m=(y3-y1)/(x3-x1)]. We know that x3 is 0, since we are trying to solve for y where that is true, so the equation becomes:

m=(y3-y1)/(-x1)

-x1*m=y3-y1

y3=y1-x1*m

y3 is really b in the standard form, since it is, by definition the intercept, or the value when x=0,

so

b=y1-x1*m -- this gives you the y intercept anytime you know the slope and one point on the line.

In the example, y1 = 4, x1=3 and we've already calculated m to be 2, so

b=4-3*2 = -2

So, the function would be

y = 2x -2

To check, plug in the values of the other point, p2, and see if they work

y2 = 2*x2 - 2

8=2*5-2

It's easier than it looks. It can help you to understand if you get some old fashioned graph paper and plot it so you can see what is happening.

Probably something like p1 = (3,4); p2 = (5,8); the general form of this is p1=(x1,y1); p2=(x2,y2). The slope in this case is rise over run, in other words, the change in y divided by the change in x. This can be calculate between these two points as (y2-y1)/(x2-x1). In my sample above, this would be (8-4)/(5-3) = 4/2 = 2 giving the value of m.

To find the value of b (the y intercept) you need the value of y when x = 0. Since you already know that m, the slope is 2, consider a new point, call it p3 (x3,y3), pick either of the known points and solve the slope equation again, this time for y3. [m=(y3-y1)/(x3-x1)]. We know that x3 is 0, since we are trying to solve for y where that is true, so the equation becomes:

m=(y3-y1)/(-x1)

-x1*m=y3-y1

y3=y1-x1*m

y3 is really b in the standard form, since it is, by definition the intercept, or the value when x=0,

so

b=y1-x1*m -- this gives you the y intercept anytime you know the slope and one point on the line.

In the example, y1 = 4, x1=3 and we've already calculated m to be 2, so

b=4-3*2 = -2

So, the function would be

y = 2x -2

To check, plug in the values of the other point, p2, and see if they work

y2 = 2*x2 - 2

8=2*5-2

It's easier than it looks. It can help you to understand if you get some old fashioned graph paper and plot it so you can see what is happening.

Jun 16, 2009 | Educational & Reference Software

the 6th term of an A.P is equal to 2.the value of common difference of the A.P which makes the product a1a4a5 least is given by

Aug 06, 2008 | SoftMath Algebrator - Algebra Homework...

91 people viewed this question

Usually answered in minutes!

where do i put the parenthesis to make this problem true: 6x4-3=8

There is no solution to this question unless you change the math rules.

(6x4)+3=21

6x(4-3)=6

(6x4-3)=21

×